Intervención del trabajador social con niños con discapacidad - Pogo Espinoza, Paola Stefania; Rodriguez Gonzales, Ingrid Betzabeth (Machala: Universidad Técnica de Machala, 2023)
This research work is oriented to publicize the Social Inclusion of Children and adolescents with disabilities in the Inclusive World Foundation in the city of Machala. Regarding our research topic and through the support of some authors based on a bibliographical investigation, it was possible to obtain that Social Inclusion is a process in search of equality and equity for people with disabilities, promoting the enjoyment of opportunities without any type of discrimination due to their physical, ethnic or economic condition. Within these opportunities is education, which is the primary basis for the development and progress of a person, which is why it is important to promote specialized education where methodologies are used according to the needs and difficulties of students with disabilities. in order for them to capture the information and teachings taught by their teachers. Within the Constitution of the Republic of Ecuador, being a supreme norm and being the basis for the formation of executive decrees, it promotes the enjoyment of rights and opportunities to all people without discrimination of any kind, also within the Code of Children and Adolescents, it is encouraged the inalienable rights of this priority group, it is also very necessary to promote the active participation of the respective family members to protect their integrity. The methodology of this research is qualitative that allows us to collect the information in a transcendent way, which is why it began with a bibliographical base about Social Inclusion and Children and Adolescents with Disabilities, to give way to the realization of a Interview with the respective interdisciplinary team in order to gain knowledge of the methodologies and tools used to work with Children and Adolescents with Disabilities. With the collection of information obtained based on the tools used, and the results can be reflected within the diagnostic parameter, therefore, the opening is given to propose an intervention proposal, which, from the perspective of a Social Worker, is Promote the use of a monitoring tool to implement it in the intervened institution to improve its performance and optimize its services.
Este trabajo de Investigación está orientado en dar a conocer sobre la Inclusión Social de los Niños, niñas y adolescentes con Discapacidad en la Fundación Mundo Inclusivo en la ciudad de Machala. En lo que respecta a nuestro tema de investigación y mediante el apoyo de algunos autores en base a una investigación bibliográfica se pudo obtener que la Inclusión Social es un proceso en busca de la igualdad y equidad para las personas con discapacidad, promoviendo el goce de oportunidades sin ningún tipo de discriminación por su condición física, étnica o económica. Dentro de estas oportunidades se encuentra la educación, que es la base primordial para el desarrollo y progreso de una persona, es por ello, que es importante que se fomente una educación especializada donde se utilicen metodologías acordes a las necesidades y dificultades de los estudiantes con el fin de que ellos logren captar la información y las enseñanzas impartidas por sus docentes. Dentro de la Constitución de la República del Ecuador siendo una norma suprema y siendo base para la formación de decretos ejecutivos promueve el goce de derechos y oportunidades a todas las personas sin discriminación de ningún tipo, además dentro del Código de la Niñez y Adolescencia se fomenta los derechos irrenunciables de este grupo prioritario, además es muy necesario que se promueva la participación activa de los respectivos familiares para que proteja la integridad de los mismos. La metodología de esta investigación es cualitativa que nos permite recopilar de manera trascendente la información, es por ello que se inició con una base bibliográfica acerca de la Inclusión Social y los Niños, Niñas y Adolescentes con Discapacidad, para dar paso a la realización de una entrevista al respectivo equipo interdisciplinario con el objetivo de tener conocimiento de las metodologías y herramientas utilizadas para trabajar con Niños, Niñas y Adolescentes con Discapacidad. Con la recopilación de información obtenidos en base a las herramientas utilizadas, y de resultados se puede reflejar dentro del parámetro de diagnóstico, por consiguiente, se da la apertura a plantear una propuesta de intervención, que, desde la perspectiva de un Trabajador Social, se fomente la utilización de una herramienta de seguimiento para implementarlo en la institución intervenida para mejorar su desempeño y optimizar sus servicios.
Keywords: INCLUSION SOCIAL; DISCAPACIDAD; METODOLOGIA; INTERVENCION